Hypoxia-induced macropinocytosis represents a metabolic route for liver cancer - Zhang, Misty Shuo; Cui, Jane Di; Lee, Derek; Yuen, Vincent Wai-Hin; Chiu, David Kung-Chun; Goh, Chi Ching; Cheu, Jacinth Wing-Sum; Tse, Aki Pui-Wah; Bao, Macus Hao-Ran; Wong, Bowie Po Yee; Chen, Carrie Yiling; Wong, Chun-Ming; et al. (Nature communications, 2022)
Hepatocellular carcinoma (HCC) invariably exhibits inadequate O 2 (hypoxia) and nutrient supply. Hypoxia-inducible factor (HIF) mediates cascades of molecular events that enable cancer cells to adapt and propagate. Macropinocytosis is an endocytic process initiated by membrane ruffling, causing the engulfment of extracellular fluids (proteins), protein digestion and subsequent incorporation into the biomass. We show that macropinocytosis occurs universally in HCC under hypoxia. HIF-1 activates the transcription of a membrane ruffling protein, EH domain-containing protein 2 (EHD2), to initiate macropinocytosis. Knockout of HIF-1 or EHD2 represses hypoxia-induced macropinocytosis and prevents hypoxic HCC cells from scavenging protein that support cell growth. Germline or somatic deletion of Ehd2 suppresses macropinocytosis and HCC development in mice. Intriguingly, EHD2 is overexpressed in HCC. Consistently, HIF-1 or macropinocytosis inhibitor suppresses macropinocytosis and HCC development. Thus, we show that hypoxia induces macropinocytosis through the HIF/EHD2 pathway in HCC cells, harnessing extracellular protein as a nutrient to survive. Cancer cells rely on macropinocytosis to scavenge extracellular proteins for growth. Here the authors show that macropinocytosis supports the survival of hypoxic hepatocellular carcinoma cells and this is dependent on HIF-1, which in turns activates the transcription of a membrane ruffling protein, EH domain-containing protein 2.